Essential entomology / George C. McGavin - McGavin, George; Davranoglou, Leonidas-Romanos (Oxford University Press, 2022)
Comprising well over half of all known animal species, insects are the most successful organisms on the planet. Indeed, it is no exaggeration to say that one cannot study agriculture, biology, and the environment, without a basic understanding of entomology. Furthermore, insects are indispensable to advances in molecular biology and genetics, and their ongoing decline in many parts of the world has stimulated much research in the crucial roles they play in global ecosystems.However, the sheer diversity of insects can be a challenge to every newcomer to entomology. Most entomology textbooks tend to focus on insect biology, leaving readers with only a superficial idea of insect diversity and evolution, while others delve into too much detail that will deter the novice. In contrast, Essential Entomology has a clear taxonomic structure that provides readers with the necessary framework to understand the diversity, life history, and taxonomy of insects in a new light. This fully revised edition provides the most up-to-date guide to insects and includes all the major developments in molecular biology and palaeontology of the last 20 years.This textbook is an essential read for undergraduate and graduate students taking courses in entomology, agriculture, and forestry. It will also appeal to a broad academic audience of ecologists, conservationists, natural resource managers, as well as to the far more numerous general readers who are interested in wildlife, nature, and the environment. With these diverse audiences in mind, the straightforward and accessible style of the first edition has been maintained, technical jargon has been kept to a minimum, and sufficient background information is provided to enable the reader to follow the text with ease. --